Role of protective Pelargonium Sidoides root extract and Curcumin on Mushroom poisoning: An Experimental study in rats - Velid Unsal,; Kurutaş EB,; Güngör M,; Aksan M Emrah, (International Journal of Phytomedicine, 2017)
Phalloidin is a cyclic heptapeptide containing cysteine amino acids. The toxicity of phallodin is attributed to the sulfur atom of the sulfur in the indole ring of the molecule and it is responsible for acute gastroenteritis occurring during the initial period of poisoning. Pelargonium sidoides, reinforcing the immune system, antiviral, has antibacterial properties as well as antioxidant properties.The aim of this study is to investigate the protective role of Pelargonium sidoides and Curcumin against mushroom poisoning. 28 Wistar albino rats were divided into four groups. Group I; Along the study, 0.2 ml saline was administered intraperitoneally to the rats .Group II (phalloidin, 0.5 mg / kg) were administered for 5 days of study. Group III : From the beginning to the end of the study, 0.5 mg / kg phalloidin i.p.,0,2 ml/kg pelargonium sidoides were administered orally. Group IV : From the beginning to the end of the study, 0.5 mg / kg phalloidin intraperitoneally,0.2 ml/kg Curcumin were administered orally.At the end of the study, the rats were sacrificed. The blood of the rats was taken. İn serum Superoxide dismutase (SOD), Glutathione peroxidase (GSH-Px), Paraxonase (PON), Arylesterase (ARE) ,Adenosine Deaminase (ADA) , Xhanthine oxidase (XO),Protein Karbonyl (PC), Malondialdehyde(MDA), Nitric oxide (NO), were measured by spectrophotometry. In Group II, MDA, , PC levels and XO activity increased significantly compared to Group I. (p<0.05).PS and Curcumin treatment ameliorated some enzyme levels (SOD, GSH-px, PON, ADA ) in serum with phalloidin induced rats. Values of Group III approached Group I. Phalloidin increases toxic ROS. Pelargonium sidoides and Curcumin are antioxidant, antitoxic. And They such as silibin can protective against mushroom poisoning.